The Relationship Between Airway Occlusion Pressure and Severity of liver Cirrhosis in Candidates for Liver Transplantation - Gholamipoor, Delara (Middle East J Dig Dis, 2020)
BACKGROUND End-stage cirrhosis is an irreversible condition, and liver transplantation is the only treatment option in for the affected patients. Respiratory problems and abnormal breathing are common findings among these patients. In this study, for the first time, we examined the relationship between the severity of liver cirrhosis and respiratory drive measured by mouth occlusion pressure (P(0.1)). METHODS This was a cross-sectional study conducted on 50 candidates for liver transplantation who were referred to the pulmonary clinic of Imam Khomeini Hospital for pre-operative pulmonary evaluations. Arterial blood gas analysis (ABG), pulmonary function tests, and measurement of P0.1 were performed for all patients. The severity of liver disease was assessed using the Model for End-Stage Liver Disease (MELD) score. RESULTS The median P(0.1) was 5 cm H(2) O. P(0.1) was negatively associated with PaCO(2) (r = -0.466, p = 0.001) and HCO3 - (r = -0.384, p = 0.007), and was positively correlated with forced expiratory volume at 1s (FEV1 )/ forced vital capacity (FVC) (r = 0.282, p = 0.047). There was a strong correlation between P(0.1) and MELD score (r = 0.750, p < 0.001). Backward multivariate linear regression revealed that a higher MELD score and lower PaCO(2) were associated with increased P(0.1). CONCLUSION High levels of P(0.1) and strong direct correlation between P(0.1) and MELD score observed in the present study are suggestive of the presence of abnormal increased respiratory drive in candidates for liver transplantation, which is closely related to their disease severity.